3D-printed Ti6Al4V scaffolds coated with freeze-dried platelet-rich plasma as bioactive interface for enhancing osseointegration in osteoporosis. (September 2020) - Qiao, Shichong; Sheng, Qianbin; Li, Zuhao; Wu, Dongle; Zhu, Yu; Lai, Hongchang; Gu, Yingxin
Abstract: The serious complications after arthroplasty in patients with osteoporosis is a challenge for orthopedics. Three-dimensional (3D)-printed porous titanium (pTi) alloys have the character of low stiffness, similar to cortical bone, and are seemed as promising materials in orthopedic applications, but limited by the bio-inert of titanium alloy. Thus, improving the bioactivity of the prosthesis and bone regeneration around the implant are crucial for the osseointegration. Herein, we established rabbit model of osteoporosis by bilateral ovariectomy, and the bioactive interface was constructed by coating 3D-printed pTi scaffolds with autologous platelet-rich plasma (PRP) prepared by traditional and Freeze-Dried methods. The pTi have advantages of ideal pore size, porosity and mechanical properties matching with bone tissue. In vitro, PRP-coated pTi significantly promoted bone marrow mesenchymal stem cells (BMSCs) attachment, proliferation, migration, and osteogenic differentiation. In vivo studies of the implant coatings were performed using osteoporosis models. The results indicated that this PRP-coated bioactive interface enhanced bone regeneration and osseointegration. Besides, compared with Traditional PRP, the Freeze-Dried PRP-coated pTi exhibited the superiority of promoting cell activity and osteogenic differentiation of BMSCs, and better bone formation. The novel Freeze-Dried PRP-coated pTi shows potential for the development of artificial prosthesis with bioactive interface for patients with osteoporosis. Graphical abstract: Unlabelled Image Highlights: 3D-printed Ti6Al4V scaffolds coated with Freeze-Dried platelet-rich plasma is fabricated as a bioactive interface. The composite scaffolds promoted OP-BMSCs attachment, proliferation, survival, migration, and osteogenic differentiation. Achieving the effect of enhancing osseointegration in osteoporosis.